Barriers to Covenantal Pluralism in Bangladeshi Public Opinion - Fair, C. Christine (The review of faith & international affairs, 2021)
In this paper, we explore Bangladeshi popular support for “covenantal pluralism,” a philosophy developed by the Covenantal Pluralism Initiative at the Templeton Religion Trust. We use a novel dataset derived from a 2017 nationally representative survey of Bangladeshi respondents which included numerous survey items germane to this study. Unfortunately, while Bangladesh may most certainly benefit from such a concept, we find little empirical evidence of popular support for its key conditions and propositions. We also find little evidence that any Bangladeshi government would pursue such a concept legally because it would undermine key sources of legitimacy which are necessary to secure the current government’s access to power and opportunities for graft.